2016
DOI: 10.1371/journal.pone.0158726
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Са2+-Binding Domain of NADPH Oxidase 5 (NOX5): Toward Understanding the Mechanism of Inactivation of NOX5 by ROS

Abstract: NOX5 protein, one of the most active generators of reactive oxygen species (ROS), plays an important role in many processes, including regulation of cell growth, death and differentiation. Because of its central role in ROS generation, it needs to be tightly regulated to guarantee cellular homeostasis. Contrary to other members of NADPH-oxidases family, NOX5 has its own regulatory calcium-binding domain and thus could be activated directly by calcium ions. While several mechanisms of activation have been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…A similar increase in intracellular ROS levels that was further enhanced by ionomycin was observed in the UACC‐NOX5 overexpressing cells by flow cytometry (data not shown). These results are in concert with previous studies that have demonstrated the enhancement of NOX5 activity by calcium ionophore, consistent with its EF‐hand Ca 2+ ‐binding domains . Extracellular H 2 O 2 production was detected using the Amplex Red reagent in conjunction with HRP.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A similar increase in intracellular ROS levels that was further enhanced by ionomycin was observed in the UACC‐NOX5 overexpressing cells by flow cytometry (data not shown). These results are in concert with previous studies that have demonstrated the enhancement of NOX5 activity by calcium ionophore, consistent with its EF‐hand Ca 2+ ‐binding domains . Extracellular H 2 O 2 production was detected using the Amplex Red reagent in conjunction with HRP.…”
Section: Resultssupporting
confidence: 90%
“…43 with previous studies that have demonstrated the enhancement of NOX5 activity by calcium ionophore, consistent with its EF-hand Ca 2+ -binding domains. 35,36,46 Extracellular H 2 O 2 production was detected using the Amplex Red reagent in conjunction with HRP. As shown in Figure 3B, NOX5 can be activated both by the protein kinase C enhancing phorbol ester PMA, 47,48 and by the Ca 2+ ionophore ionomycin to generate extracellular H 2 O 2 (P < 0.05).…”
Section: Human Melanomas and Melanoma Cell Lines As Well As Epithelmentioning
confidence: 99%
“…Recent studies suggest that oxidation of NOX5 is associated with inactivation of the enzyme. NOX5 contains cysteine and methionine residues, which are highly sensitive to oxidation (Pendyala & Natarajan, 2010 They also showed by ultraviolet circular dichroism spectroscopy that oxidation decreases NOX5 -helical content and alters the secondary and tertiary structure of NOX5 (Petrushanko et al, 2016). These processes lead to a decrease in stoichiometry of the binding domain for Ca 2+ , with a consequent decrease in enzymatic activation.…”
Section: Nox5 Oxidationmentioning
confidence: 99%
“…() demonstrated that in the presence of increased ROS, cysteine and methionine residues in the Ca 2+ ‐binding (EF) domain of NOX5 are oxidized, which causes a decrease in bound Ca 2+ . They also showed by ultraviolet circular dichroism spectroscopy that oxidation decreases NOX5 α‐helical content and alters the secondary and tertiary structure of NOX5 (Petrushanko et al., ). These processes lead to a decrease in stoichiometry of the binding domain for Ca 2+ , with a consequent decrease in enzymatic activation.…”
Section: Regulation Of Nox5mentioning
confidence: 99%
See 1 more Smart Citation